2016
DOI: 10.1016/j.joca.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The incident tibiofemoral osteoarthritis with rapid progression phenotype: development and validation of a prognostic prediction rule

Abstract: Objectives No clinical prediction rules were found for estimating the likelihood of developing incident radiographic tibiofemoral osteoarthritis with rapid progression. Such a tool would enhance prognostic capability for clinicians and researchers. Design We used two longitudinal datasets to independently derive (Multicenter Osteoarthritis Study) and validate (Osteoarthritis Initiative) a prognostic clinical prediction rule for estimating the probability of incident rapidly progressing radiographic knee OA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
5
32
0
Order By: Relevance
“…These results confirm and expand our understanding that adults with greater BMI are more likely to develop AKOA, which has been previously reported to be a significant risk factor during the first four years of the OAI [3,11]. This is the first instance where it is shown that BMI is also associated with the onset of AKOA at least 4 to 8 years later.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm and expand our understanding that adults with greater BMI are more likely to develop AKOA, which has been previously reported to be a significant risk factor during the first four years of the OAI [3,11]. This is the first instance where it is shown that BMI is also associated with the onset of AKOA at least 4 to 8 years later.…”
Section: Discussionsupporting
confidence: 90%
“…While numerous studies have evaluated AKOA with data from the OAI [1,5,6,3,2,4,10,11] they have all focused on the first four years of the cohort. By studying people with AKOA after the 48-month visit of the OAI, we could explore which modifiable risk factors are consistently present and which risk factors are unique to the timing of incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, baseline total WOMAC score (averaged from both knees) helped predict who would develop accelerated KOA in the Osteoarthritis Initiative and Multicenter Osteoarthritis Study [11]. When looking at specific symptoms, we found that people who developed accelerated KOA were more likely to report a greater symptom severity compared with those who developed common KOA in 3 symptoms: difficulty lying down, pain straightening the knee fully, and pain walking.…”
Section: Discussionmentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is typically a slowly progressive disorder. However, a subset of individuals may develop accelerated KOA, which is defined by the rapid onset and progression of disease within 4 years (from preradiographic disease to advanced‐stage disease) . Two of 3 adults with accelerated KOA transition from developing KOA to accelerated KOA in fewer than 12 months .…”
Section: Introductionmentioning
confidence: 99%
“…However, a subset of individuals may develop accelerated KOA, which is defined by the rapid onset and progression of disease within 4 years (from preradiographic disease to advanced‐stage disease) . Two of 3 adults with accelerated KOA transition from developing KOA to accelerated KOA in fewer than 12 months . Individuals with accelerated KOA have substantially greater pain and disability when compared to their peers without accelerated KOA, and this becomes evident prior to radiographic onset of the disease .…”
Section: Introductionmentioning
confidence: 99%